2021
DOI: 10.1136/bmjgh-2020-003814
|View full text |Cite
|
Sign up to set email alerts
|

Novel vaccine safety issues and areas that would benefit from further research

Abstract: Vaccine licensure requires a very high safety standard and vaccines routinely used are very safe. Vaccine safety monitoring prelicensure and postlicensure enables continual assessment to ensure the benefits outweigh the risks and, when safety problems arise, they are quickly identified, characterised and further problems prevented when possible. We review five vaccine safety case studies: (1) dengue vaccine and enhanced dengue disease, (2) pandemic influenza vaccine and narcolepsy, (3) rotavirus vaccine and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
4
0
3
Order By: Relevance
“…Dengvaxia ® , one of the most advanced developments in vaccines against dengue, raised serious safety concerns when data showed an increased risk of hospitalization in naïve vaccinees when they were exposed to natural infection [ 80 ]. Takeda vaccine TAK-003 is still in phase III trials and has been shown to be safe and to induce protection against dengue-related hospitalization with efficacies around 75–80% independent of serostatus of vaccinated individuals [ 9 ].…”
Section: Safety Issues With Dengue Vaccinesmentioning
confidence: 99%
“…Dengvaxia ® , one of the most advanced developments in vaccines against dengue, raised serious safety concerns when data showed an increased risk of hospitalization in naïve vaccinees when they were exposed to natural infection [ 80 ]. Takeda vaccine TAK-003 is still in phase III trials and has been shown to be safe and to induce protection against dengue-related hospitalization with efficacies around 75–80% independent of serostatus of vaccinated individuals [ 9 ].…”
Section: Safety Issues With Dengue Vaccinesmentioning
confidence: 99%
“…Nach Impfung gegen humane Papillomviren
Humane Papillomviren
kam es in Dänemark und Japan zu Verdachtsfallmeldungen eines komplexen regionalen Schmerzsyndroms („complex regional pain syndrome“ [CRPS]) und posturalen Tachykardiesyndroms (POTS). Groß angelegte Studien ergaben jedoch keinen Anhalt für einen statistischen Zusammenhang [ 29 , 30 ].…”
Section: Impfreaktionen Impfkomplikationen Impfschädenunclassified
“…Vor allem nach der ersten Gabe der Rotavirusimpfung
Rotavirusimpfung
tritt bei Kindern aus Ländern mit hohem und mittlerem Einkommen geringfügig häufiger eine Darminvagination auf [ 30 ]. Das Gesamtrisiko für eine Invagination bis zum Ende des ersten Lebensjahrs zeigte sich in einer Studie des PEI jedoch nicht erhöht gegenüber ungeimpften Kindern [ 31 ].…”
Section: Impfreaktionen Impfkomplikationen Impfschädenunclassified
See 1 more Smart Citation
“…4 The detection of potential AEFIs that have arisen during routine or mass vaccination campaigns led to the development of passive and active vaccine surveillance systems that were leveraged and enhanced for AEFI monitoring of COVID-19 vaccines. 4,5 While these surveillance systems have shown COVID-19 vaccines to be safe, they have also led to the identification of rare AEFIs that were not identified in prelicensure clinical trials, such as thrombosis with thrombocytopenia syndrome following adenoviral vector COVID-19 vaccines, and myocarditis following COVID-19 mRNA vaccines. 6,7 This narrative review focuses on events of myocarditis and pericarditis that occurred after COVID-19 mRNA vaccines, given the extensive use of this platform worldwide and the significant impact of this AEFI on COVID-19 vaccine campaigns and vaccine acceptance, especially in the highest risk groups.…”
Section: Introductionmentioning
confidence: 99%